Islamization Versus Deislamization of Language a Case of Indonesian Vocabularies - Maulana, M F (KnE Social Sciences, 2018)
The Islamization of language could not be deniable when Isalamization process is carried out in any cultures. Arabic language is being charged with Divine inspiration in the form of Revelation so that Arabic becomes the noblest one among the humankind’s language and it is the only divinely inspiration living language. The Islamic key concepts as represented by its worldview is encompassing some vocabularies which are use in any languages such as the words Allah (God), Rasulullah (Messenger), Jannah (Paradise), Akhirah (The Day After), iman (belief), adl ( justice), etc. In Indonesian language for example, these basic Arabic vocabularies also used as key concepts in understanding of Islam. However, because of social dynamic and developing era of politics, economics or culture in Indonesia deIslamization of language takes place as well. In fact, changing meaning of the key concepts of Islam and shifting paradigm of thoughts cause to devastating of Muslim’s religiosity. Keywords: deIslamization, key concepts, language, worldview